2020
DOI: 10.15288/jsad.2020.81.556
|View full text |Cite
|
Sign up to set email alerts
|

Addressing the Syndemic of HIV, Hepatitis C, Overdose, and COVID-19 Among People Who Use Drugs: The Potential Roles for Decriminalization and Safe Supply

Abstract: People whou se drugs (PWUD) face concurrent public health emergencies from overdoses, HIV,h epatitis C, and COVID-19, leading to an unprecedented syndemic.ResponsestoPWUDthat go beyond treatment-such as decriminalization and providing asafe supply of pharmaceutical-grade drugs-could reduce impacts of this syndemic. Solutionsa lready implemented for COVID-19, sucha se mergency safe-supplyp rescribing and providing housing to people experiencing homelessness, must be sustained once COVID-19 is contained. This pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
94
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 18 publications
4
94
0
Order By: Relevance
“…The COVID-19 pandemic also led to discontinuation of previously available services that addressed some of these barriers specific to rural syringe access, such as home peer outreach and mobile syringe exchange. While discontinuation of these services may have been a reasonable early response, as the pandemic continues programs will need to reconsider outreach services to balance risk posed by COVID-19 infection with increasing overdose and HIV/HCV transmission [ 3 8 , 22 ]. We also found that, as experienced by the participants, state guidelines allowing for needs-based syringe distribution were not uniformly realized during the study period, further limiting harm reduction engagement in the context of a rapidly changing pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic also led to discontinuation of previously available services that addressed some of these barriers specific to rural syringe access, such as home peer outreach and mobile syringe exchange. While discontinuation of these services may have been a reasonable early response, as the pandemic continues programs will need to reconsider outreach services to balance risk posed by COVID-19 infection with increasing overdose and HIV/HCV transmission [ 3 8 , 22 ]. We also found that, as experienced by the participants, state guidelines allowing for needs-based syringe distribution were not uniformly realized during the study period, further limiting harm reduction engagement in the context of a rapidly changing pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Similar measures were implemented elsewhere [ 34 , 35 ]. Additional measures were also proposed, such as improving addiction treatment access using telehealth encounters for OAT induction [ 36 , 37 ], substance use decriminalization [ 38 ], and safe supply of opioid [ 39 ] and other substances, including stimulants [ 40 ]. Further research should investigate their potential impact on substance use behaviours, substance use disorder outcomes, treatment retention, intoxications, and mortality, as well as long-term physical, mental, and social outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…The SARS-CoV-2 epidemics overlaps with endemic diseases [NCD, malaria, schistosomiasis, tuberculosis, hepatitis C, HIV, dengue and other neglected tropical diseases (NTD)] and with seasonal diseases (such as influenza and other respiratory diseases), a host of cultural and social determinants (fear, stigmatization, racism, gender, economic inequalities, mis-information, risk behaviors, food and nutrition insecurity, occupation, climate, exposure to different types of pollution, supply of health and social care services, health care seeking behavior and violence, supply of drugs and addictive behaviors) and climate and environment [ 31 , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] ] ( Fig. 1 ).…”
Section: Evidence Of the Syndemic Nature Of The Sars-cov-2 Pandemicmentioning
confidence: 99%